Testing the MODIS Thermal Modes for Dust Storms Monitoring - Jalal, Fatima; S. Mahdi, Alaa (Iraqi Journal of Physics, 2023)
Climate change is one of the global issues that is receiving wide attention due to its clear impact on all living organisms. This is essential for Iraq since it was classified as the fifth most vulnerable country to climate change. One of the manifestations of these changes in Iraq is the increasing frequency and severity of dust storms. In this study, the Normalized Difference Dust Index (NDDI) spectral index for Moderate Resolution Imaging Spectroradiometer (MODIS) sensor bands was used to measure and track the dust storm that occurred on May 16, 2022, as well as to test the validity of one of the daily products of this sensor, MOD11A1, to measure surface temperature and emissivity before and after the storm. It was found that the MOD09GA product is effective in monitoring and detecting dust storms. The areas close to the Syrian borders were identified as the origin of this storm. On the other hand, the MOD11A1 product is not suitable for daily monitoring due to the large number of missing pixels that cannot be compensated by conventional statistical methods or spatial interpolation techniques, as the percentage of missing data sometimes equals half or more of the scene, despite the fact that both products are from the same location and time of capture and under the same weather conditions. Therefore, it’s not suitable for daily monitoring of dust storm phenomena. The average of these data for eight days after image processing can be relied upon to monitor other phenomena or applications.